Personal computer usage and teasing among geographic information systems students - Adams Osman; Bismark Mensah; Clarke Ebow Yalley; Adjoa Afriyie Poku (Social Sciences and Humanities Open, 2023)
This study arose from the observation of teasing among Geographic Information Systems (GIS) students who use personal computers (PCs) during practical sessions. A review of the literature did not provide any informative knowledge on teasing based on PC characteristics. Hence, the study sought to assess the degree of teasing among GIS students, PC characteristics students are frequently teased over, types of teasing, and its positive and negative effects. Students at University of Education in Winneba (UEW), Ghana, provided data on their experiences with analysis employed being multinomial regression, binary logistic regression, the McNemar and Wilcoxon signed-rank test. The findings of the study revealed that students had experienced and engaged in various forms of teasing during GIS sessions. Low processing power of PCs and the brand type were the targets of verbal jokes among students. Teasing during lecture periods resulted in both positive and negative utility, with a greater number of students reporting net positive utility. Although the findings verified the researchers' utilitarian viewpoint, teasing needs to be regulated, as some students exhibited feelings of depression and low self-worth.